PENGELOLAAN LINGKUNGAN PADA ERA OTONOMI DAERAH DENGAN PENDEKATAN TEKNOLOGI - Widodo, Lestario (Jurnal Teknologi Lingkungan, 2004)
Experiences shown that a development program with centralistic model yields an unfair condition which cause a gap among provinces and decreasingenvironmental quality. In this autonomic era the spirits from local governments are to use natural resources as much as possible and less concern to conserve the environment. Through an application of technology, which has environmental perception and the application of clean production technology, thus, utilisation of regional natural resources could guarantee the continuity of sustainable development and prosperity of community in their local area.